Gestión administrativa en el cumplimiento de los objetivos del área de banco de sangre en un hospital, Región Amazonas 2022 - Lalangui Sarmiento, Angela Milagritos (2023)
The purpose of this research was to determine the relationship that exists between administrative management and the fulfillment of the objectives of the blood bank area in a Hospital, Amazonas Region 2022. It was based on theories related to the subject to obtain information from each of the the variables under study, the methodology was a basic study, quantitative approach, non-experimental design of correlational crosssection, the population consisted of 70 health professionals who worked in a Hospital in the Amazonas region. Likewise, the sample was the same as the population, in techniques the survey was used and as instruments the questionnaire, had as results that the administrative management is good with 40% and regular 31.4%, the level of compliance was obtained a good level of 44.3 % and regular with 28.6%. Likewise, the relationship between the administrative management variables and the achievement of objectives, indicating that Spearman's Rho obtained 0.830, a direct positive relationship. Concluding that the null hypothesis is rejected and the alternative is accepted.